Analysis of Service Quality for Transjakarta Bus Transportation Users - Effendi, Ahmad Haidar; Dawina, Fathia Ayu; Farlina, Happy Yeary; Savira, Naura; Rizka, Rizka (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to examine the quality of Transjakarta Bus service from the user’s perspective. Using a qualitative approach and descriptive survey method, data were collected from 202 respondents through an online questionnaire based on a Likert scale. This study focuses on five dimensions of SERVQUAL, namely Physical, Reliability, Responsiveness, Assurance, and Empathy. The results of thematic analysis show that many respondents emphasize the importance of physical comfort of the bus, punctuality of service, and official interaction as the main factors in assessing their satisfaction. Responsiveness and empathy from officers are the two dimensions that most influence positive user views. This study also found obstacles such as lack of information about routes and the number of passengers exceeding the limit, which often become obstacles in the travel experience. The conclusion of this study is that improvements in the aspects of responsiveness, assurance, and clear information delivery to passengers have the potential to increase user satisfaction and loyalty to Transjakarta services. As a recommendation, it is suggested that Transjakarta management improve the accuracy of bus schedules, enhance officer training in customer service, and optimize fleet distribution during peak hours to address waiting time issues and improve overall service quality.